The Awareness of Diseases Caused by Parasites, Methods of Prevention, and their Relationship to the Educational Level - Salwa Muftah Eljamay; Marwa A. Ramadan Bumaluma; Fatma Muftah Eljamay (African Journal of Advanced Pure and Applied Sciences, 2023)
Parasitic infections are the most prevalent diseases in the world, predominantly in developing countries, aimed to know about the Libyans’ awareness of parasites and their prevention and the relationship between educational level and awareness. Material and Methods: A cross-sectional questionnaire survey was conducted A set of 11 questions including questions on knowledge and awareness of the mode of transmission of vector-borne diseases among the general population. The questions were uploaded in google forms. Results: the Frequency and Percent % of the independent variables, that the Female 225(83.3%), Males 51(16.7%), ages between 15 and 65, The highest level of education for university graduates, 173(56.5%), and the lowest percentage of students in high school 6(2.0%), as for the job, it was higher for 93(30.4), the number and proportions of answers to questions about parasite awareness and the resulting diseases and ways of preventing them, where the highest percentage is yes , Libya’s daily practices in buying vegetables and drinking water, the highest percentage was for drinking mineral water 171(55.9%), the source of vegetables is Greenery market 165(53.9%), in the highest percentage was for those who were not infected 183(59.8%), followed by Intestinal Infection 63(20.6%), Skin Infection 59(19.3%) and Sexual Infection 1(0.3), there are strong relationship between the Education Level and knowledge p-value (0.002 < 0.005), X2 (105.463), R (0.178**), and there are not relationship between Education Level Behaviours p-value (0.741 > 0.005), R (0.019), X2(32.670(.Conclusion: there is a strong correlation between the level of education and the extent to which Libyan citizens are about parasite-borne diseases, methods of infection and methods of prevention.